PENGARUH LAMA PENYINARAN LAMPU LED (Light Emitting Diode) TERHADAP PERTUMBUHAN TANAMAN MICROGREENS BUNGA MATAHARI (Helianthus annuus L.) PADA BERBAGAI MEDIA TANAM - Saniatus Solekhah; Nora Augustien K; Bambang Prijanto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[THE EFFECT OF LIGHT EMITTING DIODE (LED) IRRADIATION DURATION ON THE GROWTH OF SUNFLOWER (Helianthus annuus L.) MICROGREENS PLANT ON VARIOUS PLANTING MEDIA]. The conversion of agricultural land into residential and office buildings causes a decrease in agricultural land every year so the development of indoor plant cultivation with the concept of urban farming, such as microgreens. Microgreens are plants in the period after germination, usually between 7-14 days. Microgreens have a nutrient content of at least 40 times higher than when they are fully grown. Sunflower plants are one of the plants that have been developed as microgreens. Sunflower (Helianthus annuus L.) is an introduced plant from America. This flower is bright yellow with a large flower head with a diameter of up to 30 cm. LED light is used to help the plant growth process that is carried out indoors. This research was conducted indoors is located in Bratang Wetan 1 No. 19c, Wonokromo, Surabaya from March 2021 to May 2021. The method used in this research is a Completely Randomized Design (CRD) system consisting of 2 factors with 3 replications. The first factor is the length of irradiation which consists of 4 levels of treatment and the second factor is the type of planting media which consists of 3 levels of treatment. The results showed that the combination of 16 hours irradiation time with soil planting medium was able to increase the growth of Sunflower microgreens plants on the variables of cotyledon width, wet weight, dry weight, and chlorophyll test.